Vitamin D and bronchopulmonary dysplasia in preterm infants - Joung, K. E.; Burris, H. H.; Marter, L. J. Van; McElrath, T. F.; Michael, Z.; Tabatabai, Patrik; Litonjua, A. A.; Weiss, S. T.; Christou, H. (Journal of perinatology, 2016)
Vitamin D deficiency is associated with asthma and reactive airway disease in childhood but its potential contribution to bronchopulmonary dysplasia (BPD) in preterm infants is unknown. Preterm infants have lower levels of 25-hydroxyvitamin D (25(OH)D) at birth and are at risk for nutritional deficiencies after birth. The objective of the study was to evaluate the association of 25(OH)D concentrations at birth and at 36 weeks’ corrected gestational age with BPD in preterm infants born before 29 completed weeks of gestation. We collected umbilical cord blood samples from 44 preterm infants (gestational age <29 weeks) delivered at Brigham and Women’s Hospital in Boston. In addition, with parental consent we collected venous samples at 36 weeks’ corrected age from 20 preterm infants born before 29 weeks’ gestation (including 6 infants with previously collected cord blood). Samples were frozen at −80 °C until subsequent measurement of 25(OH)D levels by chemiluminescence. We used multivariable logistic models to adjust for gestational age and considered other confounding variables, including maternal race, age, mode of delivery and infant sex. Among 44 infants, 41 (93.2%) survived and 3 (6.8%) died before 36 weeks’ corrected age. Median 25(OH)D levels at birth were 30.4 ng ml−1 in preterm infants who subsequently died or developed BPD and 33.8 ng ml−1 in infants who survived without BPD (P=0.6). Median 25(OH)D levels at corrected age of 36 weeks were 59.0 ng ml−1 among survivors without BPD and 64.2 ng ml−1 among survivors with BPD (P=0.9). Neither cord blood nor 36 weeks’ corrected 25(OH)D levels were associated with odds of death or BPD (adjusted odds ratio (OR) 1.00, 95% confidence interval (CI): 0.73 to 1.37; and OR 0.93, 95% CI: 0.61 to 1.43, respectively). Among this population of extremely preterm infants neither cord blood nor the 36 weeks’ corrected age 25(OH)D levels were associated with development of BPD. Notably, at the current level of supplementation, all extremely preterm infants in our cohort had achieved 25(OH)D levels >30 ng ml−1 by 36 weeks’ corrected age, which is thought to represent sufficiency in adult and pediatric populations.
Gesehen am 06.05.2020